2002
DOI: 10.1034/j.1600-0404.2002.0o138.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of patients with low-grade astrocytomas and medically intractable seizures

Abstract: Resections of low-grade astrocytomas in patients with medically intractable seizures are safe procedures that effectively control seizures in the majority of patients, resulting in significant improvement in the patients' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Given the significant impact of epilepsy on a patient's quality of life, improved control of seizures is an important treatment objective in patients with LGG. [43][44][45] Remission of seizures has a substantial effect on the cognitive and social ability of patients, which is liable to reduce the burden on families and society. To our knowledge, the mechanism of postoperative seizure control is poorly understood; and the results from different studies have been rather inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant impact of epilepsy on a patient's quality of life, improved control of seizures is an important treatment objective in patients with LGG. [43][44][45] Remission of seizures has a substantial effect on the cognitive and social ability of patients, which is liable to reduce the burden on families and society. To our knowledge, the mechanism of postoperative seizure control is poorly understood; and the results from different studies have been rather inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection has been particularly effective at controlling medically refractory seizures, resulting in near-seizure-free status, or a substantial reduction in seizure frequency and intensity, in nearly all patients. 32,33 Although large preoperative tumor size (diameter >5-6 cm) is consistently identified as a poor prognostic factor for survival, 3,6 the effect on clinical outcome of reduced tumor size remains controversial, and several studies have produced inconsistent results (Table 1) www.nature.com/clinicalpractice/neuro resection on outcomes in low-grade glioma and found that a preponderance of modern studies support extensive resection over biopsy alone. 19 Leighton and co-workers, who retrospectively studied 167 consecutive patients treated at the London Regional Cancer Centre, ON, Canada, for low-grade glioma over a period of 16 years found, on both univariate and multivariate analysis, that minimal postoperative residual tumor was associated with significantly improved 5-year OS (82% vs 64%; P = 0.008 on univariate analysis, P = 0.006 on multivariate analysis).…”
Section: Ncpneuro_2007_148f1epsmentioning
confidence: 99%
“…The first of these is an obvious one. Regarding the other objectives, retrospective series suggest that surgery may improve the neurological condition and the control of seizures [18,26,27]. There are no randomized trials in LGG on the impact of extent of resection on survival.…”
Section: Treatments Of Low Grade Gliomamentioning
confidence: 99%